Governance and management under Tomorrow's schools : dualism or separatism? : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Educational Administration, Department of Social and Policy Studies in Education at Massey University, Palmerston North, New Zealand - Taylor, Annette May (Massey University, 2001)
The thesis aimed to determine the following: (i) How boards of trustees and principals in state secondary schools determine their respective roles and responsibilities of governance and management. (ii) Can the principal be seen as standing apart from the board of trustees of which they are a member? (iii) If conflicts between governance and management arise, how are these solved? The researcher was concerned to learn in educational readings that governance and management and the governance-management interface is a sorely neglected area of research, and that since the inception of Tomorrow's Schools there had been an exponential growth in the number of court proceedings involving conflicts of governance and management between principals and boards of trustees. The researcher wanted to determine the views of principals and board chairpersons on governance and management and undertake an in-depth study of a sample of secondary schools' governance-management interface. A considerable body of quantitative and qualitative research literature has examined the background to the educational reforms and the delivery and implementation of the 'self-management' model. Of particular relevance to this study is the fact that New Zealand followed the 'New-Right' philosophy that was sweeping other westernised countries and devolved the responsibility and accountability for the provision of education to local communities. Empowerment of local communities was seen to be an essential ingredient in ensuring that the 'self-management' model succeeded. Evidence in this study suggests that the roles of governance and management are not truly split as was envisaged by the initiators of the educational reforms. There appears to be a merging of the two roles and negotiation of the two roles is needed between the principal and the board of trustees. The governance-management interface that has been developed over the last decade has done so owing to each school's interpretation of Tomorrow's Schools guidelines and the relevant sections of the Education Act 1989. While the participants in this study indicate a satisfaction with their governance-management interface, there are dissatisfactions with the current model and these have been recorded. The majority of the participants in this study see the principal as an integral part of the board, despite the fact that he/she is both an employee of the board and an employer of staff. Conflict between the two roles had occurred and the schools were able to deal with these in-house or by providing professional development in the areas of concern. In the researcher's opinion, if schools wish to ensure that the governance and management of their school is run in such a way that the board governs and the principal manages, then aspects ofJohn Carver's (1997) Policy Governance model provides them with a vehicle to do so. This model sharpens the board's focus on governance and the ends they wish to achieve, and provides the principal with empowerment to develop and implement the means needed to achieve the prescribed ends. The current model of governance and management is working for the majority of schools. However, the "one glove fits all approach" is not appropriate for all schools. Evidence in this study shows that there does need to be a reappraisal of some issues that surround the 'self-management' model. Because schools exist to promote teaching and learning and the board of trustees and principals are charged with the responsibility for showing gains in student learning, ways must be found to further enhance the governance and management functions.
Keywords: School management and organisation; New Zealand; School boards; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education